'I hope I don't intrude' : privacy and its dilemmas in nineteenth-century Britain - Vincent, David, 1949- (Oxford University Press, 2015)
Taking his title from the catch-phrase of the eponymous hero of the 1825 play 'Paul Pry', a huge success in London, New York, and around the English-speaking world, David Vincent explores the worlds of privacy and celebrity in 19th-century Britain, examining debates about mass communication and state surveillance that link to today's concerns.